Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan - Wanda Wahidah; Rayuwanto (Journal of Trends Economics and Accounting Research, 2023)
This research activity aims to determine the extent to which the influence that arises from testing the price and service quality variables on customer satisfaction at the Larie48cosmtic Sampit store. This activity involved one hundred people from the people of Sampit City who had visited and purchased cosmetic products at the Lariez48cosmetic store. This study belongs to the type of quantitative study. The use of primary data in this study is from data obtained from several questionnaires that have been distributed. Sampling used a non-probability sampling method, using a purposive sampling technique. It can be seen from the results of the hypothesis testing in this research activity that the value of the adjusted r-square is 61.6% which is categorized as moderate due to achieving more than the adjusted r-square value namely 33%. And the results of the t-test showed that price had no effect on customer satisfaction while the value on the p-value on service quality was 0.000 <0.05 which stated that it had a positive and significant effect on customer satisfaction.